2022
DOI: 10.1093/bjsopen/zrac064
|View full text |Cite
|
Sign up to set email alerts
|

Modified ligation procedure for prolapsed haemorrhoids versus stapled haemorrhoidectomy for the management of symptomatic haemorrhoids (MoLish): randomized clinical trial

Abstract: Background The aim of this study was to compare a modified ligation procedure versus stapled haemorrhoidectomy (SH) in patients with symptomatic haemorrhoids. Methods This randomized trial included patients with symptomatic haemorrhoids treated in Shanghai from May 2018 to September 2021. Eligible patients were randomly 1:1 assigned the modified ligation procedure for prolapsed haemorrhoids (MLPPH) and SH groups. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Nevertheless, there is substantial clinical evidence to support that triple-line stapling with three-row staplers performed better than double-line stapling with two-row staplers for the treatment of prolapsing hemorrhoids, especially to prevent recurrences for at least 5 years [9]. In a recent randomized clinical trial, the short-term outcomes of a modified hemorr hoidal transanal arterial ligation technique and stapled hemorrhoidopexy method were compared at Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai [18]. The study found similar trends in the reduction of postoperative pain and prevention of symptom recurrence using a disposable PAH 32 stapler (Brightness Medical Device Co., China) for the stapled surgery (hematochezia, prolapse, and rectal pain).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is substantial clinical evidence to support that triple-line stapling with three-row staplers performed better than double-line stapling with two-row staplers for the treatment of prolapsing hemorrhoids, especially to prevent recurrences for at least 5 years [9]. In a recent randomized clinical trial, the short-term outcomes of a modified hemorr hoidal transanal arterial ligation technique and stapled hemorrhoidopexy method were compared at Putuo Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai [18]. The study found similar trends in the reduction of postoperative pain and prevention of symptom recurrence using a disposable PAH 32 stapler (Brightness Medical Device Co., China) for the stapled surgery (hematochezia, prolapse, and rectal pain).…”
Section: Discussionmentioning
confidence: 99%